Pengaruh Citra Merek dan Kualitas Pelayanan terhadap Loyalitas Pelanggan pada Yourdayflower di Bangkinang - Rahmad Akbar; Dzulhijjah Yetti; Hayatul Khairul Rahmat; Andri Nofiar. Am; Nurkholis (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study was designed to explore the extent to which the strength of brand image and the standards of service quality are able to solidify customer loyalty at Yourdayflower in Bangkinang. Adopting a quantitative approach with an associative research design, this study involved 98 customers as respondents who contributed data through a structured questionnaire. All collected data were processed using multiple linear regression analysis via SPSS, having successfully passed a series of prerequisite tests including validity, reliability, and classical assumption tests to ensure model accuracy. The empirical findings reveal that all research indicators possess a high level of reliability. Furthermore, the established model proved to meet the standards of normality and is free from the disturbances of multicollinearity and heteroscedasticity. Statistically, both brand image and service quality demonstrate a positive contribution toward customer loyalty, both when tested independently (partially) and collectively (simultaneously). A compelling discovery in this research is that service quality plays a more crucial and prominent role than brand image in anchoring customer loyalty. These findings offer practical implications for the management of Yourdayflower to consistently prioritize service refinement and the strengthening of brand identity as strategic steps in creating harmonious, long-term relationships with their clientele.